Is Smoking Queer? Implications of California Tobacco Denormalization Strategies for Queer Current and Former Smokers. Issue 4 (2nd April 2020) - Sanders, Emile; Antin, Tamar; Hunt, Geoffrey; Young, Malisa
ABSTRACT: This article is concerned with normative conceptions of health structuring tobacco control strategies designed to "denormalize" tobacco use. Analysis of 201 interviews with non-heterosexual and/or non-cisgender adults in California revealed that participants implicated tobacco use in exacerbating health inequities and perpetuating harmful narratives of queer suffering, but also regarded smoking as a critical tool for self-care and symbol of resistance. Participant narratives suggest that using stigma in health promotion efforts which reinforce normative conceptions of health may be harmful to queer people whose social identities exist within ongoing legacies of pathology, health stigma, and deviance from hegemonic structural norms.